Adaptive Comparative Judgment and Psychological Safety in Accounting Education - Bartholomew, Scott R; Jones, Matthew D.; Hawkins, Steven R.; Orton, Jeff (Journal of Education and Training, 2022)
Traditional Accounting curricula include instruction on the preparation of audit documentation, however, experiential instruction for students on the process of review-both as a reviewer and reviewee-is often scarce or missing. This study investigated a classroom intervention that engaged undergraduate students in peer-review activities to gauge how peer review and feedback impacted student performance and their perceptions of being able to engage in interpersonal risks. Using a case-method approach, students developed audit workpapers that were later peer-reviewed through a digital system utilizing adaptive comparative judgment (ACJ). Students’ achievement scores were collected, and students also completed a pre/post survey on psychological safety. Our results indicate that student psychological safety increased over the course of the semester; however, the peer review process through ACJ did not significantly improve student performance within the class. The students responded positively to the intervention as an engaging learning process and effective in teaching real-world skills. Thus, this intervention provides an example of how peer review activities could enhance the learning experience for students.